The Village SDGs? Can Partnership Aspect Enhance the Economic Development in Pangandaran Village? - Jayanti Armida Sari (Universitas Lambung Mangkurat, 2023)
This study describes the implementation of SDG programs through partnerships to improve economic development in Pangandaran villages. This research adopts qualitative research method and case study design. A qualitative approach was used because this study aims to analyze how the SDG program builds the economy in Pangandaran village through partnerships. Furthermore, the case study approach was chosen because this study focuses on partnership policies in the SDGs. The data obtained in this study are in the form of primary and secondary data. Primary data were obtained using purposive sampling techniques. To obtain primary data, semi-structured and unstructured interviews were conducted. Secondary data comes from other sources through literature research. The stages of data analysis are data consideration, data display, and drawing and verifying conclusions. The analysis revealed that one of the SDG programs, the partnership aspect, has been implemented in Pangandaran village to promote economic development. However, there are still some obstacles in the implementation process. This is reflected in several aspects such as cooperation with third parties, availability of Internet access in villages, village statistics and goods export activities.